The simulacra of "Lost" realities- A Baudrillardian postmodernism study of 17 Parokya ni Edgar songs - Cloquingan, Shirine C. (2007.)
The Simulacra of "Lost" Realities - A Baudrillardian Postmodernism study of 17 Parokya ni Edgar songs is written to analyze the songs of Parokya ni Edgar using Jean Baudrillard's concept of the simulacrum. It aims to identify some dominant postmodern poetics reinforced in the songs of Parokya ni Edgar and discuss the different simulacra reflected in these songs. This analysis starts by reviewing relevant literatures through library and internet researches. The songs are randomly taken from different albums. Surprisingly, the songs reveal that they reinforce not one but three important postmodern poetics. They also present many simulacra that may challenge some of our long-held ideas. The simulacra are there to hide the fact that the real is no longer real.
Thesis (Undergraduate, Bachelor of Arts in Literature) - University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Songs -- Parokya ni Edgar